PERENCANAAN MESIN PEMERAS SANTAN SISTEM SCREW KAPASITAS 10 LITER/MENIT DENGAN SEMI AUTOMATIC LOADER - Ficky Ali Murfiqin; Artono Raharjo; Unung Lesmanah (Jurnal Teknik Mesin, 2013)
Process squeeze coconut milk in food processing especially baking today many use traditional mechanisms is by squeezing the grated coconut by hand. In the process of using coconut milk squeeze mechanism that determines the quality of the milk, squeeze the coconut milk in the traditional way (squeeze by hand) are found to be efficient and hygienic because it takes a long time and the results obtained did not meet health requirements. With the design and manufacture of coconut milk extractor Machine Screw System Capacity 10 liters / min With Semi Automatic Loader is expected to facilitate the process of extortion coconut cake so that the processing time is more hygienic and also achieved more efficiently. For specifications of the machine scew extractor of Santan System Capacity 10 liters / min With Semi Automatic Loader is used as propulsion electric motor with a 1400 rpm spin n1, n2 140 rpm with power 0.186 KW and transmitted using gear type gear straight.